The Influence of Project Scheduling Effectiveness and Administrative Efficiency on the Performance of Telecommunication Tower Construction Management at PT Dayamitra Telekomunikasi, Tbk Regional Office Central Sumatra - Pitri Rahmadani Harahap; Kurniani Kurniani; Achmad Zaenuddin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The performance of infrastructure development management is one of the important aspects in the successful implementation of projects, especially in the telecommunications sector which requires punctuality, administrative efficiency, and good work coordination. This study aims to analyze the influence of project scheduling effectiveness and administrative efficiency on the performance of telecommunication tower construction management at PT Dayamitra Telekomunikasi Tbk, Regional Office Sumbagteng. The study uses a quantitative approach with a sampling technique in the form of saturated sampling of the entire population totaling 31 respondents. Data collection was carried out through observation, literature study, and the distribution of questionnaires that have gone through validity and reliability tests. The data analysis methods used included classical assumption tests, multiple linear regression analysis, hypothesis tests, and determination coefficients with the help of SPSS version 25 application. The results of the study show that the effectiveness of project scheduling and administrative efficiency have a positive and significant influence on the management performance of telecommunication tower construction. Based on the results of multiple linear regression analysis, the equation Y = –0.445 + 0.568X₁ + 0.439X₂ was obtained, which shows that any improvement in project scheduling effectiveness and administrative efficiency will improve the performance of development management. The value of the determination coefficient (R²) of 0.622 indicates that the two independent variables contribute 62.2% to the performance of development management, while the remaining 37.8% is influenced by other factors outside the study. Thus, companies need to improve the accuracy of project scheduling and optimal administrative management to support the success of telecommunication infrastructure development.